Using the fringing electric field in microfluidic volume sensors to enhance sensitivity and accuracy - Riordon, Jason; M.-Catafard, Nicolas; Godin, Michel (Université d'Ottawa | University of Ottawa, 2012)
The particle trajectory above impedance-monitoring coplanar electrodes in a microfluidic channel dramatically influences the measuredelectric current change. We use finite element modeling to predict changes in ionic current for microspheres flowing in highly fringing fields, and validate these results by introducing a buoyancy-based particle focusing technique. Using 6 μm polystyrene particles in solutions of varying density, we control the height of the particle trajectories near the sensing electrodes and show that sensitivity can be increased by up to 3.5× when particles flow close to the electrodes compared to particles flowing further away, while simultaneously improving accuracy.
Keywords: microfluidic; volume sensor; coulter; buoyancy; electric field